(3GdMeGjI GdbGfhfjI ddGSJKeGQGJ GdGLfHjI GdeHGTQI hJShjI GdefGRYGJ GdNGUI HgG (B/s - (3QeVGf Ydj YHO GdcQje OShbj YGeQs; (3YHO GdMajX YHOGddg YjO (B: s; (3eMehO eNJGQ HQjQj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2009)
(3Gf MeGjI GdGSJKeGQGJ GdGLfHjI GdeHGTQI ef GdeNGWQ ZjQ GdJLGQjI jbJVi JbQjQ fhYjI ef GdhSGFd GdNGUI HgPg GdMeGjI agfGc GdhSGFd GdNGUI HGdMeGjI GdehVhYjI ef fGMjI(B: (3hGdhSGFd GdNGUI HGdMeGjI GdGLQGFjI ef fGMjI GNQi(B. (3hGjG eG cGf GdGeQ aGf aGYdjI GdMeGjI GdehVhYjI ddGSJKeGQGJ GdGLfHjI GdeHGTQI Yf WQjb GdJTQjYGJ GdOGNdjI hGdeYGgOGJ hGdGJaGbjGJ GdOhdjI Gh ZjQgG ef hSGFd gPg GdMeGjI Gf jJCJi Ydi hLgg GdGced GdG GPG GbJQf HGdMeGjI GdGLQGFjI(B. (3hdGgejI GdMeGjI GdGLQGFjI ddGSJKeGQGJ GdGLfHjI GdeHGTQI(B: (3hGROgGQ fXGe GdJMcje(B: (3agh jYJHQ GdhSjdI GdGcKQ aGYdjI hGdeKdi dJShjI efGRYGJ GdGSJKeGQs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2009.s
(3JTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B502 - 525.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGSJKeGQ GdCLfHj GdeHGTQ s; (3MeGjI GdGSJKeGQs; (3YbO GdGSJKeGQs; (3TQW GdKHGJ GdJTQjYjs; (3TQW EYGOg GdJaGhVs; (3GdJCejf Ydi GdGSJKeGQ GdCLfHjs; (3GdJMcje GdJLGQi GdOhdjs; (3ELQGAGJ GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs